2022
DOI: 10.1155/2022/7523333
|View full text |Cite
|
Sign up to set email alerts
|

Caristi’s Fixed Point Theorem in Cone Metric Space

Abstract: In this paper, we provide a short, comprehensive, and brief proof for Caristi-Kirk fixed point result for single and set-valued mappings in cone metric spaces. In addition, we partially addressed an open problem in which Caristi-Kirk fixed point result in cone metric spaces reduces to a classical result in metric spaces and provided a brief justification for a partial positive answer to this open problem using Caristi-Kirk fixed point theorem on uniform space. The proofs given to Caristi-Kirk’s result vary and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Lael et al [3] introduced a method for the Caristi-Kirk fixed point result for single mappings in conical metric spaces with a simple yet complete argument. The results of this research showed that the Caristi-Kirk fixed point in conical metric spaces turns into a result similar to traditional methods in reduced metric spaces.…”
Section: Introductionmentioning
confidence: 99%
“…Lael et al [3] introduced a method for the Caristi-Kirk fixed point result for single mappings in conical metric spaces with a simple yet complete argument. The results of this research showed that the Caristi-Kirk fixed point in conical metric spaces turns into a result similar to traditional methods in reduced metric spaces.…”
Section: Introductionmentioning
confidence: 99%